Pengaruh Upah Minimum Regional dan Pengangguran terhadap Tingkat Kemiskinan (Studi Kasus 35 Kab./Kota di Jawa Tengah Tahun 2021) - Wafirrotullaela Wafirrotullaela; Anton Bawono (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2023)
AbstractPoverty is the government's main problem which is thought to be caused by the Minimum Wage and the unemployment rate in an area. This study aims to determine the effect of the Minimum Wage (U) and the unemployment rate (P) on the poverty level. This type of research is a quantitative study with a sample of 35 districts/cities in Central Java Province. The analysis technique used is multiple linear regression with the help of the SPSS program. With a significance level of 5%, the t-test results show that partially the Minimum Wage (U) has a negative effect on poverty while the unemployment rate has no effect on the poverty level. The F test shows that the Minimum Wage (U) and the unemployment rate together have a significant positive effect on the poverty level.Keyword: Minimum Wage, Unemployment, poverty